Cemetery dance - Preston, Douglas J. (Preston, Douglas J. Pendergast novel., 2009)
After New York Times reporter William Smithback and his wife Nora Kelly, a Museum of Natural History archaeologist, are brutally attacked in their apartment on Manhattan's Upper West Side, Pendergast--the world's most enigmatic FBI Special Agent--returns to New York City to investigate a murderous Obeah cult.